Work Order for ceramic brick paving including patent stone base in the ground floor and granite installation on the academic stairs of Brac University new campus building - Brac University (Brac University, 2023)
This work order has been made between Brac University and Harbour Developments & Construction Ltd. for ceramic brick paving including patent stone base in the ground floor and granite installation on the academic stairs of Brac University new campus project.